Attitudes on technological, social, and behavioral economic strategies to reduce cellphone use among teens while driving. (18th August 2018) - Delgado, M. Kit; McDonald, Catherine C.; Winston, Flaura K.; Halpern, Scott D.; Buttenheim, Alison M.; Setubal, Claudia; Huang, Yanlan; Saulsgiver, Kathryn A.; Lee, Yi-Ching
ABSTRACT: Objective : The majority of U.S. teens admit to handheld cellphone use while driving, an increasingly common cause of crashes. Attitudes toward novel cellphone applications and settings that block use while driving are poorly understood, potentially limiting uptake. We examined teens' willingness to reduce cellphone use while driving and perceptions of potential strategies to limit this behavior. Methods : Teen drivers ( n = 153) aged 16–17 who owned smartphones and admitted to texting while driving completed an online survey. Survey instruments measured willingness to give up cellphone use and perceptions of technological and behavioral economic strategies to reduce cellphone use while driving. We used chi-square tests to test the hypothesis that willingness to give up certain types of cellphone use while driving and the perceptions of strategies to reduce cellphone use while driving would differ by self-reported frequency of texting while driving in the past 30 days (low [1–5 days] vs. high [6 or more days]). Results : Most teens were willing or somewhat willing to give up reading texts (90%), sending texts (95%), and social media (99%) while driving. However, they were not willing to give up navigation (59%) and music applications (43%). Those who engaged in high-frequency texting while driving were more likely to say that they were not willing to give up navigation applications (73 vs. 44%, P <.001), music applications (54 vs. 32%, P <.001), and reading texts (15 vs. 4%, P =.029). Overall, the following strategies where rated as likely to be very effective for reducing texting while driving: gain-framed financial incentives (75%), loss-framed financial incentives (63%), group-based financial incentives (58%), insurance discounts (53%), automatic phone locking while driving (54%), e-mail notifications to parents (47%), automated responses to incoming texts (42%), peer concern (18%), and parental concern (15%). Those who engaged in high-frequency texting while driving were less likely to say that following strategies would be very effective: automated responses to incoming texts (33 vs. 53%, P =.016), peer concern (9 vs. 29%, P =.002), and parental concern (9 vs. 22%, P =.025). The strongest perceived benefit of cellphone blocking apps was decreasing distraction (86%). The predominant reason for not wanting to use this technology was not wanting parents to monitor their behavior (60%). Conclusions : Promising strategies for increasing acceptance of cellphone blocking technology among teen drivers include automated screen locking and permitting hands-free navigation and music combined with behavioral economic incentives to sustain engagement.